Effect of bentonite characteristics on the elemental composition of wine - Catarino, Sofia (2013)
Physical, chemical, and mineralogical characteristics of six bentonites were assessed and related to their elemental release to wine. Extraction essays of bentonites in wine at three pH levels were carried out. The multielemental analysis of bentonites and wines was performed by atomic absorption spectrometry (AAS) and inductively coupled plasma mass spectrometry (ICP-MS). Bentonite addition resulted in significantly higher concentrations of Li, Be, Na, Mg, Al, Ca, Sc, V, Mn, Fe, Co, Ni, Ga, Ge, As, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Ba, W, Tl, Bi, and W. In contrast, the concentrations of B, K, Cu, Zn, and Rb significantly decreased. A strong correlation between Na concentrations of treated wines and its content in bentonite exchange complex was observed. Al and Fe contents reflected bentonite extractable aluminous and ferruginous constituents, while Be, Mg, Ca, V, Mn, Ni, Ge, Zr, Nb, Mo, Sn, Sb, Tl, Pb, and U concentrations reflected the elemental composition of bentonites. Several nonconformances with OIV specifications demonstrated the need for an effective control.